The evolution of canon law in the church of Englad: from the act of supremacy to the canons of the church of England - Kilanowski, Igor (Vergentis, 2024)
The study explores the axiological, theological, and doctrinal underpinnings of Canon Law in the Church of England, alongside the historical development of Anglican legal philosophy. It includes references to state law, acknowledging its impact on the Anglican community. The article culminates in a historical analysis of modern canon law formation within the Canons of the Church of England. It concludes by emphasizing the importance of ecclesiastical communities having autonomy in shaping their own laws, free from external influences.